2006
DOI: 10.1073/pnas.0507656103
|View full text |Cite
|
Sign up to set email alerts
|

Dual strategies for peptidoglycan discrimination by peptidoglycan recognition proteins (PGRPs)

Abstract: The innate immune system constitutes the first line of defense against microorganisms in both vertebrates and invertebrates. Although much progress has been made toward identifying key receptors and understanding their role in host defense, far less is known about how these receptors recognize microbial ligands. Such studies have been severely hampered by the need to purify ligands from microbial sources and a reliance on biological assays, rather than direct binding, to monitor recognition. We used synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
88
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 50 publications
0
88
0
Order By: Relevance
“…5). The binding and structural studies previously carried out with LPS and LTA (4) (40). It has been shown that PGRP-S binds to both Lys-type and DAP-type PGNs (41).…”
Section: Discussionmentioning
confidence: 99%
“…5). The binding and structural studies previously carried out with LPS and LTA (4) (40). It has been shown that PGRP-S binds to both Lys-type and DAP-type PGNs (41).…”
Section: Discussionmentioning
confidence: 99%
“…PGRP-S preferentially binds DAP-type PGN (Swaminathan et al, 2006). In mollusks, rCfPGRPS1 showed high affinity to Lys-type PGN from S. aureus (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thermodynamic parameters for the binding of PGRPs to PGN derivatives were determined using a MicroCal VP-ITC titration calorimeter as described in ref. 20. For the present titrations, c values (the product of the initial PGRP concentration and K b ) ranged from 3.06 to 7.99, allowing for precise determination of K b (19,36).…”
Section: Pgn Derivatives Procedures For Synthesizing Pgn Analogs Nag-mentioning
confidence: 99%
“…5), indicating only a minor contribution from the NAG moiety present in both GMPP and GMPP 2 , but not in MPP. Neither PGRP-I␤C nor -I␣C bound MPP-Dap, even under conditions at which interactions with K b Ͼ100 M Ϫ1 should be detectable (19,20). Thus, both these PGRP domains appear highly specific for Lys-type PGN.…”
mentioning
confidence: 94%